2015
DOI: 10.1007/s00294-015-0476-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional analysis of the pathogenicity-related gene VdPR3 from Verticillium dahliae on cotton

Abstract: The fungal plant pathogen Verticillium dahliae is the causal agent of vascular wilt, a disease that can seriously diminish cotton fiber yield. The pathogenicity mechanism and the identity of the genes that interact with cotton during the infection process still remain unclear. In this study, we investigated the low-pathogenic, non-microsclerotium-producing mutant vdpr3 obtained in a previous study from the screening of a T-DNA insertional library of the highly virulent isolate Vd080; the pathogenicity-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…With the completion of the genome sequence of V. dahliae 3642, ATMT technology has been more widely used for the study of V. dahliae genes that are associated with diverse phenotypes181920, especially the genes associated with pathogenicity. At present, several genes associated with pathogenicity have been identified from the mutants with reduced or lost pathogenicity18192122, confirming that ATMT is an effective method to identify the genes associated with V. dahliae pathogenicity.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…With the completion of the genome sequence of V. dahliae 3642, ATMT technology has been more widely used for the study of V. dahliae genes that are associated with diverse phenotypes181920, especially the genes associated with pathogenicity. At present, several genes associated with pathogenicity have been identified from the mutants with reduced or lost pathogenicity18192122, confirming that ATMT is an effective method to identify the genes associated with V. dahliae pathogenicity.…”
Section: Discussionmentioning
confidence: 65%
“…Pathogenicity assays identified several mutants with reduced or lost pathogenicity, and the candidate genes were involved in V. dahliae pathogenicity. The genes included VdHMGS (encoding hydroxymethyglutaryl-CoA synthase), VdEG-1 (encoding endoglucanase), VdGPIM3 (encoding glycosylphosphatidylinositol mannosyltransferase 3), and VdMFS1 (encoding major facilitator superfamily transporter)18; VdGARP1 (encoding glutamic acid-rich protein)19; VdPR3 (pathogenicity-related gene 3)21 and VdCYC8 (encoding CYC8 glucose repression mediator protein)22. These results suggest that ATMT can be effectively used to identify genes that are associated with pathogenicity of V. dahliae .…”
mentioning
confidence: 99%
“…As our understanding of the pathogenicity of V. dahliae increases, it appears that a variety of genes are required for virulence towards host plants, including protein kinases (Rauyaree et al ., ; Tian et al ., ; Tzima et al ., ), TFs (Luo et al ., ; Santhanam et al ., ; Sarmiento‐Villamil et al ., ; Tran et al ., ; Xiong et al ., ), effectors (de Jonge et al ., ; Liu et al ., ; Santhanam et al ., ), enzymes involved in plant cell wall degradation (Chen et al ., ; Liu et al ., ; Maruthachalam et al ., ) and other functional genes (Gao et al ., ; Klimes and Dobinson, ; Li et al ., ; Maruthachalam et al ., ; Santhanam et al ., ; Zhang DD et al ., ; Zhang YL et al ., ). In this study, we identified a new pathogenicity and virulence‐related gene encoding a Fungal_trans domain‐containing TF (Figs and ).…”
Section: Discussionmentioning
confidence: 97%
“…Several V. dahliae pathogenicity-related genes have been identified de Jonge et al, 2012de Jonge et al, , 2013Liu et al, 2013Liu et al, , 2014Maruthachalam et al, 2011;Zhou et al, 2012). In addition, several pathogenicity-related genes have been identified using T-DNA insertion mutagenesis (Gao et al, 2010;Li et al, 2015;Luo et al, 2016;Maruthachalam et al, 2011;Santhanam et al, 2017;Zhang DD et al, 2016;Zhang YL et al, 2015. Collectively, these studies indicate that the processes associated with pathogenicity are complex, and that a variety of V. dahliae gene products are required for host infection.…”
Section: Introductionmentioning
confidence: 99%
“…Genes associated with the formation of microsclerotia include VMK1 , VDH1 , Vdgrp1 , VdSNF1 , VdNLP , and VdPR3 . All of these genes have been shown to positively regulate microsclerotia development, and knock-outs of each of these genes resulted in reduced microsclerotia formation [3, 611]. VdPKAC1 and VGB have been shown to negatively control microsclerotia development, and disruption of each of them improved microsclerotia development [12, 13].…”
Section: Introductionmentioning
confidence: 99%